(untitled) - Phillips, Diane (Oxford, 1999)
The book contains practical, tried amd tested ideas and materials for planning, organisazing, and carrying out project work with children aged 5 to 13. It combines language and skills development with activities that will challenge young learners and motivates them to be independent.
Keywords: English language; Textbooks for foreign speakers